Some mismatch repair activities in Escherichia coli. - Radicella, J P (1988)
Heterozygous bacteriophage lambda DNA molecules, whose replication requires mismatch correction of a mutant nucleotide in the transcribed strand, provide an assay for localized mismatch repair in Escherichia coli. We describe two systems: one removes the A in C.A or G.A mismatches and the other removes one or the other C in a C.C mismatch. Mutations disabling the first system result in a mutator phenotype that may be identical to mutY.